2016
DOI: 10.1016/j.chb.2016.05.017
|View full text |Cite
|
Sign up to set email alerts
|

A parental perspective on apps for young children

Abstract: Touchscreen applications (apps) for young children have seen increasingly high rates of growth with more than a hundred thousand now available apps. As with other media, parents play a key role in young children's app selection and use. However, to date, we know very little about how parents select apps for their children. Guided by uses and gratification theory, a survey was conducted with 600 Dutch parents who had at least one child between three and seven years old. Across two studies, we identified parents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
49
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 48 publications
5
49
1
Order By: Relevance
“…The survey data were collected by a large research institute in the Netherlands (GfK). This data collection was part of a larger project from which other data have been published elsewhere ( Broekman et al, 2016 ). Parents were recruited through GfK’s existing online panel (approximately 50,000 households) that is representative of the Netherlands.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The survey data were collected by a large research institute in the Netherlands (GfK). This data collection was part of a larger project from which other data have been published elsewhere ( Broekman et al, 2016 ). Parents were recruited through GfK’s existing online panel (approximately 50,000 households) that is representative of the Netherlands.…”
Section: Methodsmentioning
confidence: 99%
“…In order to maximize the likelihood of parents selecting particular apps, it is crucial that these features map onto the expressed needs of parents. Research has shown that parents have specific needs when it comes to selecting apps for their child ( Broekman et al, 2016 ). First, and most prominent, they desire apps that are entertaining but at the same time foster independent play (need for independent entertainment).…”
Section: Child-centered App Designmentioning
confidence: 99%
See 3 more Smart Citations